Black Box Testing Using the Equivalence Partitions Technique to Test the Functionality of the Ternaku.id Website - Arif Amrulloh; Abednego Dwi Septiadi; Maryona Septiara; Pramudya Adi Wicaksono (Universitas Amikom Purwokerto, 2023)
A data validation process that is not optimal can result in inappropriate data stored in the database, such as a login process that can cause errors. This can be detrimental to website owners and users, so it is necessary to improve the quality of more accurate validation. The ternaku.id website, which has been designed in such a way, must go through a testing stage to ensure the quality of the software itself. A good test case is if the test has the possibility of finding an uncovered error. In this research, functionality testing will be carried out using black box testing using the Equivalence Partition method. This method test solves or divides the input domain of the program into data classes so that test cases that are considered relevant enough to test the registration or registration functionality, login, and investment application features on the Ternaku can be obtained.id website. The results of tests carried out on 11 functions showed that 3 functions failed and 8 functions succeeded.